Pharmaceutical and Biological Evaluation of Nano Photosensitizers for Cancer Therapy - Sundara Raj, Behin (Curtin University, 2018)
This study demonstrated the effects of novel hybrid metal oxide nanoparticles as an effective nano-photosensitizer for the photodynamic therapy against melanoma in vitro and in vivo. A strong synergistic effect was produced by the hybrid NPs and UV-A irradiation. The hybrid nanoparticles modified with folic acid enhanced cellular uptake and exhibited strong anti-tumour activity alone and with UV-A. These hybrid nanoparticles provide us better understanding in designing the semiconductor metal oxides-based nano-photosensitizers for photodynamic therapy.